Warrior's dishonour barbarity, morality and torture in modern warfare - Kassimeris, George (Ashgate, 2006)
The characteristic act of men at war is not killing. It is killing by committing shocking and unspeakable atrocities, when circumstances permit. What drives ordinary people into hatred, genocide, inhumanity and evil? What turns friends and neighbours against each other with such savagery? Where does such barbarity come from? This collection examines the anarchy, cruelty and overwhelming confusion of modern warfare. In particular it analyzes: what happens when morality vanishes from the battlefield and why torture is endemic in modern warfare; how human rights, in times of war, lose meaning as a set of principles; whether official propaganda and enemy demonization make barbaric behaviour easier; and how we can develop cultures opposed to torture that damage the legitimacy of our societies. Through a wealth of case studies that have been carefully selected in terms of their themes, approaches and methodologies, this comprehensive volume provokes discussion and enhances understanding from a variety of disciplinary perspectives.